2009
DOI: 10.1111/j.1748-8583.2009.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Employee voice: does union membership matter?

Abstract: Industrial relations research has traditionally viewed trade unions as the primary mechanism for employee voice. With the decline in unionism in many advanced industrial economies over the past two decades, new direct non‐union voice mechanisms have been introduced by employers. This focus on the mechanisms for employee voice, however, fails to take account of employees' perceptions of voice. We suggested that employee perceptions of voice vary between the different levels of an organisation and proposed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 67 publications
(112 reference statements)
2
31
0
1
Order By: Relevance
“…Even where employee voice is legally protected by trade unions, however, GLBT employees can still remain silent. As Benson and Brown (2010) noted, unions differ in their capacity to represent their members. Research by Morehead, Steele, Alexander, Stephen, and Duffin (1997) demonstrated that only 24% of unionized workplaces in Australia were characterized as active, with senior delegates present, membership meetings held, and negotiations taking place between management and labor.…”
Section: Voice Mechanisms For Glbt Employeesmentioning
confidence: 99%
See 1 more Smart Citation
“…Even where employee voice is legally protected by trade unions, however, GLBT employees can still remain silent. As Benson and Brown (2010) noted, unions differ in their capacity to represent their members. Research by Morehead, Steele, Alexander, Stephen, and Duffin (1997) demonstrated that only 24% of unionized workplaces in Australia were characterized as active, with senior delegates present, membership meetings held, and negotiations taking place between management and labor.…”
Section: Voice Mechanisms For Glbt Employeesmentioning
confidence: 99%
“…Various mechanisms provide employees with the opportunity to express their voice (Benson & Brown, 2010). Among these are legal regulations, trade unions, and specific GLBT and human rights organizations, which will be explored in this section.…”
Section: Voice Mechanisms For Glbt Employeesmentioning
confidence: 99%
“…And the receiver responds to the message. Researches also support that employee voice is a two-way communication where information is exchanged [9,21,43]. The parts written in Italics refer to one-way communication; decisions of employees whether to stay or exit and employees' reaction toward the organization when he or she decided to stay unwillingly.…”
Section: Communication Theorymentioning
confidence: 99%
“…The role of union in the presence of HR department is quite ambiguous and unnecessary because HR department supports individual employee voice, information sharing, collective decision making, and employee participation [42][43][44]. For the decline of unionization in organizations, two major reasons are widely documented in literature [41,45,46].…”
Section: Modern Employee Voicementioning
confidence: 99%
See 1 more Smart Citation